Efficacy of local anaesthetic peri-femoral artery injection compared to subcutaneous infiltration in combination with femoral and sciatic nerve blocks for reducing thigh tourniquet-induced hypertension during lower-limb surgery under general anaesthesia: A randomised controlled double-blinded trial - Chonruethai Tangkittithaworn; Wirinaree Kampitak; Tanawat Benjamungkalarak; Jirun Apinun (Indian Journal of Anaesthesia)
Background and Aims: Tourniquet-induced hypertension (TH) remains an unresolved issue. Various techniques, such as peripheral nerve blocks, peri-femoral artery blocks, and subcutaneous infiltration, have been explored to address this. The primary objective was to compare the incidence of TH during lower-limb surgery under general anaesthesia between peri-femoral artery block and subcutaneous infiltration, combined with femoral and sciatic nerve blocks. Secondary objectives included intraoperative intravenous fentanyl and antihypertensive uses, as well as postoperative pain scores. Methods: This single-centre, double-blind, randomised controlled trial involved 58 patients scheduled for elective lower-limb surgery. Participants were assigned to the peri-femoral artery block (P-FAB) or subcutaneous infiltration (SI) groups. All patients received general anaesthesia alongside femoral and sciatic nerve blocks. TH was defined as a 30% increase in systolic blood pressure from baseline. Pain was assessed using a numerical rating scale in the post-anaesthetic care unit and at 4, 8, 12, and 24 h post-surgery. Unpaired t-test, Chi-square, and Mann-Whitney U test were used for analysis. A P value less than 0.05 was considered to be statistically significant. Results: There were no significant differences in the incidence of TH between the P-FAB and SI groups (P = 1.00). Similarly, no significant differences were observed in intraoperative fentanyl (P = 0.459) or antihypertensive use (P = 0.992). Pain scores across all measured aspects, including thigh and incision sites, were also not significantly different between groups (P > 0.05). Conclusions: In lower-limb surgery, adding a peri-femoral artery block to general anaesthesia with femoral and sciatic nerve blocks did not reduce the incidence of TH compared to subcutaneous infiltration.